Coping strategies and correlations with depressive symptoms among female nurses working in Japanese general hospitals - Kubo, Hideyuki; Kaneko, Yoshiyuki; Saitoh, Kaori; Furihata, Ryuji; Jike, Maki; Otsuka, Yuichiro; Uchiyama, Makoto; Suzuki, Masahiro (Frontiers in Public Health, 2025)
IntroductionPreventing depression among nurses is a critical issue from the perspective of occupational welfare, but associations between depressive symptoms in nurses and stress-coping strategies remain unclear.MethodsIn the present study, an epidemiological study was conducted based on a cross-sectional questionnaire survey. Data obtained from 2,534 female nurses working at three general hospitals in Tokyo, Japan, were analyzed. Participants completed a questionnaire comprising 42 items, including depressive symptoms and stress-coping strategies, in addition to sociodemographic information and perceived mental stress.ResultsOur study showed that the emotional distraction strategy “Engaging in hobbies or relaxing” was negatively associated with both depressed mood and loss of interest. In addition, the problem-solving strategy “Making an effort to think optimistically” was negatively associated with loss of interest. Conversely, use of avoidant strategies was positively associated with both depressive symptoms.DiscussionOur findings may indicate the importance of focusing on types of coping styles when developing strategies to prevent depressive symptoms in nurses.